Direct dual-template synthesis of HZSM-5 zeolite for enhanced p-xylene selectivity in toluene methylation with CH3Br. Issue 5 (21st February 2017) - Xie, Jun; Chen, Lang; Wang, Wu-Hui; Wang, Peng; Au, Chak-Tong; Yin, Shuang-Feng
Abstract : HZSM-5 catalysts of different crystal sizes directly synthesized by a single-step method using TPAOH and TEA as templates were characterized by XRD, SEM, N2 adsorption–desorption and NH3 -TPD techniques. Abstract : HZSM-5 catalysts of different crystal sizes directly synthesized by a single-step method using TPAOH and TEA as templates were characterized by XRD, SEM, N2 adsorption–desorption and NH3 -TPD techniques. The as-synthesized zeolites show excellent catalytic activity towards the methylation of toluene with CH3 Br. The catalyst denoted as HZSM-5(30, 10) shows the highest p -xylene yield, giving a toluene conversion of 44.8% and a p -xylene selectivity of 48.5%. It was found that the increase in the amount of surface mid-strong and strong acid sites enhances the toluene conversion and the selectivity to p -xylene is determined by the amount of strong acid sites as well as the crystal size of the catalysts.